Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2001
DOI: 10.1145/365024.365121
|View full text |Cite
|
Sign up to set email alerts
|

The impact of eye gaze on communication using humanoid avatars

Abstract: In this paper we describe an experiment designed to investigate the importance of eye gaze in humanoid avatars representing people engaged in conversation. We compare responses to dyadic conversations in four mediated conditions: video, audio-only, and two avatar conditions. The avatar conditions differed only in their treatment of eye gaze. In the random-gaze condition the avatar's head and eye animations were unrelated to conversational flow. In the informed-gaze condition, they were related to turn-taking d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(128 citation statements)
references
References 16 publications
3
125
0
Order By: Relevance
“…In studies, the importance of rendering fidelity was examined for interpersonal communication [19]. Results suggest that emotions, such as embarrassment, fear, irritation, and self-awareness, could be elicited in real people by virtual characters [4].…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…In studies, the importance of rendering fidelity was examined for interpersonal communication [19]. Results suggest that emotions, such as embarrassment, fear, irritation, and self-awareness, could be elicited in real people by virtual characters [4].…”
Section: 4mentioning
confidence: 99%
“…There were three male and three female medical students (three 3 rd years and three 4 th years) and one 3 rd year female physician assistant student. All had substantial prior experience with standardized patients (at least 5, average: [10][11][12][13][14][15][16][17][18][19][20]. Five had experiences with standardized patients with AAP, and six had experiences with real patients with AAP.…”
mentioning
confidence: 99%
“…Garau et al (2001) conducted an experiment designed to investigate the importance of eye gaze in humanoid avatars representing people engaged in conversation and found that an avatar whose gaze behaviour is related to the conversation would improve the quality of communication compared to one whose gaze behaviour is random.…”
Section: Interplay Between Emotions and Avatars In Collaborative Envimentioning
confidence: 99%
“…A seven point Likert scale was used, ranging from "−3" (strongly disagree) to "3" (strongly agree), with "0" as the neutral attitude. Fifteen questions in the dimensions face-to-face, involvement, co-prescence and agent evaluation have been borrowed from [5], the engagement dimension was derived from the description in [18]. Interestingly, the only significant results relate to questions that address the salient feature of each version in a quite direct way.…”
Section: Resultsmentioning
confidence: 99%
“…Our operationalization of 'mindfulness' is based on the concepts of "face-to-face"(communication), "involvement", "co-presence", and "partner evaluation" proposed in [5], and "engagement" as described in [18].…”
Section: Theorymentioning
confidence: 99%